Industry 4.0 and the Digital Transformation of International Business - Singh, Gurinder; Goel, Richa; Garg, Vikas (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
The book throws light on the ongoing trends in international business, integration of information technology with global businesses, its role in value co-creation, resource integration, and service for service exchange. While discussing the issues of these areas, chapters of this book also delve into prevalent problematic areas which are closely related like employment, ethical aspects, power creation, and so on. Recognizing the role digitization and new technologies play in enabling global managers to communicate with outside world directly via digital channels irrespective of their location (which is especially true in time of COVID-19), the book takes an emerging economy perspective and throws light on new theories, perceptions, employment opportunities, and innovative ideas through its content. The book not only discusses effects of information technology but also the latest emerging technology in global business like use of artificial intelligence, robotics, machinelearning, big data, and their integration with the global business 4.0. Since emergence of these new technologies requires proper infrastructural development, the book also throws light on government initiatives and CSR in this respect. It contains takeaways for both undergraduate and graduate students, researchers and academicians, industry watchers, practitioners, start-ups, and entrepreneurs.
Part1: International Business Trends and Practices in the New Digital Age -- Chapter 1: Role and Importance of Information Technology in Global Business today -- Chapter 2: Changing face of International Business in the new Information Age 4.0 -- Chapter 3: International Production and Digital Economy -- Chapter 4: Global connectivity's knowledge complexities during the new information age -- Chapter 5: Expanding International Business via Smart Cities -- Chapter 6: Case Study -- Part 2: Understanding Entrepreneurial Strategies in Industry 4.0 -- Chapter 7: International Business and Block Chain Ventures -- Chapter 8: Rise of Entrepreneurship/Intrapreneurship during digital age -- Chapter 9: Mapping Global competitors during the new information age -- Chapter 10: New Digital Layers of Business Relationship -- Chapter 11: Role of Emerging Technologies like AI/ML/IOT with Reference to Industry 4.0 -- Chapter 12: Business Model: Alibaba vs Amazon etc -- Part 3: Functional Strategies in International Business in New Information Age -- Chapter 13: Internationalization through Digitization: Role of E-Businesses and E-Commerce -- Chapter 14: Changing Structure of Consumer Buying behavior and Expectation in the Digital Era -- Chapter 15: Understanding the Technology in the Developed World of Industry 4.0 -- Chapter 16: Corporate Social Responsibility and Environment responsibility in the Technology Management -- Chapter 17: Intellectual Property Rights around the Globe -- Part 4: Infrastructural Development and Societal Role with respect to Emerging Technology -- Chapter 18: The Future of Productivity and Growth of Infrastructural development -- Chapter 19: Government Implications on Infrastructural development & CSR with respect to Industry 4.0 -- Chapter 20: Societal Role and Responsibilities of the Emerging Technology in the Digital Transformation of International Business -- Chapter 21: Future roles of business in society: The expanding boundaries of International Business.
Keywords: Business information services; Technological innovations; International business enterprises; Big data; Information technology -- Management; Electronic commerce; IT in Business; Innovation and Technology Management; International Business; Big Data; Business IT Infrastructure; E-Business.